An Evaluation of the Textual Edition of KITAB AL-MAWT WA KITAB AL-QUBUR - Sunarwoto Sunarwoto (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2009)
This article deals with the textual edition of the Kita>b al-Mawt wa Kita>b al-Qubu>r by Ibn Abi> al-Dunya>, one of the great Arab writers of the third century of Hijra. It is not easy to deal with this works, since it is written not on the basis of its manuscript copies which are not available. It is Leah Kinberg of University of Hayfa, Jerusalem, who has made such a great attempt at reconstructing the Kita>b. Given the absence of original manuscript copies, it would be questionable whether the result is reliable. The term “reconstruction” itself is open to a lot of questions. The number of material covered is a case in point. Kinberg’s laborious endeavour to present this edition should be appreciated, since she offers not only a made-product but also an interesting process through which the edition comes to being as it is. This article seeks to appreciate and evaluate to what extent Kinberg’s edition offers important principles in reconstructing and editing scattered source material. The author concludes that the absence of manuscript copies has made Kinberg difficult to reach an original version, or to build even a stemma. Any doubt and suspicion are justifiable and understandable. However, by exploring the “secondary” manuscripts, she has succeeded in building her own method, regardless of its inadequacy, and her endeavour has met a scholarly standard. This is not an “ideal text” edition as the Anglo-American school has put it, but, unfortunately, it meets German school’s orientation in the sense that this edition does not pretend to be original